Sulfurization Engineering of One‐Step Low‐Temperature MoS2 and WS2 Thin Films for Memristor Device Applications. (7th October 2021) - Gu, Yuqian; Serna, Martha I.; Mohan, Sivasakthya; Londoño‐Calderon, Alejandra; Ahmed, Taimur; Huang, Yifu; Lee, Jack; Walia, Sumeet; Pettes, Michael T.; Liechti, Kenneth M.; Akinwande, Deji
Abstract: 2D materials have been of considerable interest as new materials for device applications. Non‐volatile resistive switching applications of MoS2 and WS2 have been previously demonstrated; however, these applications are dramatically limited by high temperatures and extended times needed for the large‐area synthesis of 2D materials on crystalline substrates. The experimental results demonstrate a one‐step sulfurization method to synthesize MoS2 and WS2 at 550 ° C in 15 min on sapphire wafers. Furthermore, a large area transfer of the synthesized thin films to SiO2 /Si substrates is achieved. Following this, MoS2 and WS2 memristors are fabricated that exhibit stable non‐volatile switching and a satisfactory large on/off current ratio (10 3 –10 5 ) with good uniformity. Tuning the sulfurization parameters (temperature and metal precursor thickness) is found to be a straightforward and effective strategy to improve the performance of the memristors. The demonstration of large‐scale MoS2 and WS2 memristors with a one‐step low‐temperature sulfurization method with simple strategy to tuning can lead to potential applications such as flexible memory and neuromorphic computing. Abstract : Large‐area MoS2 and WS2 thin films are synthesized via a one‐step low‐temperature sulfurization. The film quality depends directly on thickness control of the metallic precursors and the sulfurization temperature and time. The sulfurized film‐based memristors show stable non‐volatile switching and satisfactory on/off ratio. Tuning the sulfurization parameters is found to be a direct method to improve the key memristor metrics.